Psychological Well-Being of Students from Intact Families: Kesejahteraan Psikologis pada Mahasiswa dari Keluarga Tidak Utuh - Lestari, Ririn Puji; Widyastuti, Widyastuti (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this research is to find out the psychological well-being of the college students of the incomplete family, either because the father died or the parents divorce and didn’t live with the father. In this study, researcher used a qualitative approach focused on a phenomenon, the incomplete family. The subject of this research are three college students who lost their father in death or divorce and every subjects has two significant others or informans. The data collection used semi-structured interview and observation with anecdotal record. The result of this research shows that subject I can emerges five dimensions of psychological well-being which are self acceptance, positive relations with others, environmental mastery, purpose in life, and personal growth. Subject II and III they emerge all six dimensions of psychological well-being which are self acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth. The factors that affect all three subjects are the same: age, culture, social status, and social support.